Implementation Policy Allowance Islamic Religious Education Teacher Profession at the Ministry of Religion of the City - Millam Permatasari; Ardiyan Saptawan; Andries Lionardo; Raniasa Putra (Jurnal Pemerintahan dan Politik Lokal, 2026)
Implementation policy allowances the teaching profession is effort government for increase the welfare and professionalism of non-civil servant Islamic Religious Education (PAI) teachers under the Ministry of Religion. Although has arranged in Regulation of the Minister of Religion Number 43 of 2014, its implementation at the level area Still face various constraints . Research This aim analyze implementation of PMA No. 43 of 2014 concerning distribution Allowance Non-PNS PAI Teacher Profession at the Ministry of Religion of Palembang City and factors that influence it. Research use approach qualitative descriptive with technique data collection through interviews, observations, and documentation. Data analysis was carried out using the Miles, Huberman, and Saldaña model with framework implementation George C. Edwards III's policies. Research results show that implementation policy has walk Enough good, especially in the aspect communication and disposition implementer. However, the limitations source strengths and weaknesses coordination inter-agency Still become obstacle main. Therefore that, is necessary strengthening coordination and improvement capacity source Power For optimize distribution allowance in a way effective and fair.